HUBUNGAN SELF EFFICACY TERHADAP KECEMASAN BERBICARA DI DEPAN UMUM PADA MAHASISWA PROGRAM STUDI PSIKOLOGI UNIVERSITAS BUNDA MULIA - Dian Kasih; Shanty Sudarji (Universitas Bunda Mulia, 2012)
The purpose of study is to look at the relationship between self-efficacy and public speaking anxiety in Psychology students of Bunda Mulia University. Bandura (Warsito, 2004) defines self-efficacy is an individual belief that he managed to do something in a certain situation. Bandura (1986) explaines that there are three components, self-efficacy magnitude, generality and strength. Muchlas (in Ghufron & Risnawita, 2011) defines that the term anxiety as a subjective experience of mental distress tensions and pressures that accompaied by conflict or threat. There are three components of public speaking anxiety expressed by Dacey and Fiore (2002), psychological, physiological and social. The subject of this study were Psychology students of Bunda Mulia University force from 2008 to 2011. The study was conducted using quantitative methods. The data was collected by spreading questionnaire. Based on research results, obtained by the correlation coefficient of -0.658, it can be concluded that there is a relationship between self-efficacy with public speaking anxiety in Psychology students of Bunda Mulia University Study, is accepted. The lower self-efficacy that some one has, the higher anxiety public speaking. Keyword: Self-efficacy, anxiety public speaking, Psychology Student Program of Bunda Mulia University